Spanish dagger - Albert, Susan Wittig (New York : Berkley Prime Crime, 2007)
Between the herb shop, the catering business, and a weekend paper-making class, China Bayles has her work cut out for her. And now China's half-brother is opening up old wounds, trying to investigate their father's supposedly accidental death, and her husband is taking on the case-meaning she's just bound to get involved.
Keywords: Bayles, China (Fictitious character); Women detectives -- Texas; Herbalists; Texas; Mystery fiction